Cais@law ; Computerized accounting information system for small law firms in Malaysia - Zuhairah Ariff, Abd Ghadas; Fatimah, Ghazali; Mumtazimah, Mohamad; Ahmad Hadi Farhan, Khairu Azua; Wan Nursyahida, Wan Ismail (2018)
Cais@ Law is developed to assist law students to learn basic accounting of a legal firm via computerised system. Cais@Law merely requires basic Windows operating system to enable the firm to record their financial transactions on daily basis. It has three modules, which are Client Data Module, Office Account Module and Client Account Module. The documents such as voucher, receipt, invoice, bank statement and client’s data will be the input for the Cais@Law. Other than for teaching and learning purposes, Cais@Law is also designed to assist small law firms in Malaysia to manage the financial transactions, monitor the firm’s performance, record the cash inflow and outflow of clients account and facilitate the auditing process. The report produced by Cais@ Law could be used by the lawyers for submission to the professional body as evidence of a good account keeping by the firms.